Pengetahuan Dan Sikap Wanita Terhadap Kanker Serviks : Scoping Review - Ngaisah Tri Rahayu; Khairulisni Saniati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Background: Cervical cancer is the fourth most common disease of the female reproductive system worldwide. The incidence of cervical cancer in the world is entering a critical period, where every year the incidence of cervical cancer is increasing. Until now, cervical cancer is the leading cause of death in developing countries. Aim: To find out about women's knowledge and attitudes towards cervical cancer. Method: Scoping review using Arksey and O'Malley frameworks, using databases from PubMed, EBSCO and Wiley. Result: A total of 14 articles from 2016-2021 used critical appraisal from JBI (Joanna Briggs Institute). Women's knowledge and attitudes towards cervical cancer have six themes. The first theme is knowledge about cervical cancer which consists of knowledge about risk factors, signs and symptoms and early detection of cervical cancer. The second theme is the attitude of women towards cervical cancer consisting of positive and negative attitudes. The third theme is the factors that influence knowledge consisting of age, education, family income and sexual frequency. The fourth theme of factors that influence attitudes is age and education. The fifth theme of information sources consists of mass media, family and friends, health workers and health services. Theme six is the barriers to accessing information and services consisting of a lack of awareness and the high cost of vaccination. Conclusion: Knowledge about cervical cancer in women is still low. Women only have a general idea of cervical cancer. However, women show a good attitude about cervical cancer screening, because cervical cancer can cause death and if early diagnosis of the disease is very helpful in preventing disease.